GLIADIVSKA STRATA: PROBLEMS OF THE ESTABLISHMENT AND VALIDY - KYSELEVYCH, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Establishing of Gliadivska strata of Paleocene in the region of Kaniv dislocations instead of Alb and Senoman strata does not fit existing biostratigraphical data and have been carried out with the infringement of rules of existing Stratigraphic Codex of Ukraine and as a result is not valid.